AVULSION FRACTURES OF THE ANTERIOR ILIAC SPINE IN CHILDREN AND ADOLESCENTS: CLINICAL OUTCOMES OF NON-OPERATIVE TREATMENT - Božović , Aleksandar; Jovanović, Saša; Petrović, Dušan; Denović, Predrag; Tabaković, Dejan; Dulić, Oliver; Milinkov, Milan; Lalić, Ivica (Sanamed, 2025)
Objective: Avulsion fractures of the anterior iliac spine are injuries typically seen in physically active children and adolescents. There is no clear consensus regarding the optimal treatment, particularly concerning the degree of fragment displacement that warrants surgical intervention. Aim: The aim of this study was to analyze the clinical outcomes of non-operative treatment of pelvic avulsion fractures in adolescents and to examine the relationship between patient age and rehabilitation duration. Patients and Methods: A retrospective study was conducted on 12 adolescent patients with radiographically confirmed pelvic avulsion fractures. Data on age, fracture location, injury mechanism, treatment, and rehabilitation duration were collected and analyzed. All patients underwent non-operative management consisting of rest, analgesics, and crutch-assisted ambulation, followed by physical therapy. Results: All patients were male, with a mean age of 12 years. The most common fracture site was the anterior inferior iliac spine (66.6%). All fractures healed without complications. Rehabilitation duration tended to be shorter in younger patients. Functional outcomes were excellent, with all patients returning to their pre-injury activity levels. Conclusion: Non-operative treatment is an effective and safe approach for managing pelvic avulsion fractures in adolescents, even in cases with fragment displacement up to 15 mm. It provides excellent functional recovery without complications, supporting its use as the first-line treatment in this population.